2021
DOI: 10.1111/ijcp.13788
|View full text |Cite
|
Sign up to set email alerts
|

Cardiac arrhythmias amongst hospitalised Coronavirus 2019 (COVID‐19) patients: Prevalence, characterisation, and clinical algorithm to classify arrhythmic risk

Abstract: Objectives A significant proportion of COVID‐19 patients may have cardiac involvement including arrhythmias. Although arrhythmia characterisation and possible predictors were previously reported, there are conflicting data regarding the exact prevalence of arrhythmias. Clinically applicable algorithms to classify COVID patients' arrhythmic risk are still lacking, and are the aim of our study. Methods We describe a single‐centre cohort of hospitalised patients with a positive nasopharyngeal swab for COVID‐19 du… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
50
0
6

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(58 citation statements)
references
References 26 publications
2
50
0
6
Order By: Relevance
“…Of the 783 studies identified from the literature search (216 on Pubmed and 567 on EMBASE), 31 studies were selected according to the inclusion and exclusion criteria and included in the analysis [ 3 , 10 , 11 , 12 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 ] ( Figure S1 in Supplementary Materials ), with a total of 187,716 COVID-19 patients. Baseline characteristics of the studies included are reported in Table 1 .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Of the 783 studies identified from the literature search (216 on Pubmed and 567 on EMBASE), 31 studies were selected according to the inclusion and exclusion criteria and included in the analysis [ 3 , 10 , 11 , 12 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 ] ( Figure S1 in Supplementary Materials ), with a total of 187,716 COVID-19 patients. Baseline characteristics of the studies included are reported in Table 1 .…”
Section: Resultsmentioning
confidence: 99%
“…Thirteen studies were held in Europe [ 10 , 11 , 25 , 29 , 31 , 33 , 37 , 39 , 42 , 43 , 44 , 47 , 50 ], nine in North America [ 3 , 28 , 30 , 32 , 41 , 45 , 46 , 49 , 51 ], four in Asia [ 26 , 34 , 35 , 48 ], and five in other geographical locations, including one multinational study [ 12 , 27 , 36 , 38 , 40 ]. Twenty-five studies were observational retrospective [ 3 , 10 , 12 , 26 , 28 , 30 , 31 , 32 , 34 , 35 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 ], four were based on prospective observational analysis of single center cohorts [ 11 , …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Arytmie skutočne patria medzi najčastejšie KV komplikácie COVID-19 (vyskytli sa v 7,4 -16,7 %) (44,45), špecificky u seniorov (n = 339, priemerný vek 71 rokov) boli zachytené v 10,4 % (bez sínusovej tachykardie), pričom to bolo podstatne častejšie u zosnulých než žijúcich (20,6 vs 8,1 %, p < 0,001) (34). Incidencia arytmií pri COVID-19 rastie s jeho klinickou závažnosťou a vekom pacientov (46).…”
Section: Covid-19 a Arytmieunclassified
“…Zdá sa, že najčastejšou arytmiou de-novo vzniknutou počas COVID-19 je fibrilácia predsiení (AF; napríklad u 390 COVID-19 pacientov v Izraeli AF tvorila 80 % novovzniknutých porúch rytmu) (46). Z praktického hľadiska je jednou z rozhodujúcich situácií súbeh AF, tromboprofylaxie (ktorá je u seniorov apriórne indikovaná častejšie ako v mladšom veku) a hemokoagulačnej nerovnováhy, ktorú COVID-19 typicky navodzuje -všeobecné odporúčania meritórnych spoločností nateraz nie sú k dispozícii, preto sa pri indikovaní antikoagulácie zatiaľ budeme prikláňať k individuálnemu posudzovaniu jej rizík u COVID-19 seniora.…”
Section: Covid-19 a Arytmieunclassified